2021
DOI: 10.1186/s43014-021-00053-1
|View full text |Cite
|
Sign up to set email alerts
|

Thymol ameliorates ammonium toxicity via repressing polyamine oxidase-derived hydrogen peroxide and modulating ammonium transporters in rice root

Abstract: Background Ammonium is an indispensable nutrient for crop growth, but anoxic conditions or inappropriate fertilizer usage result in the increase in ammonium content in soil. Excessive ammonium causes phytotoxicity. Thymol is a kind of natural phenolic compound with anti-microbial properties. However, little is known about the role of thymol in modulating plant physiology. Here we find the novel role of thymol in protecting rice from ammonium toxicity. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…In the present study, we assessed the responses of two wheat cultivars, NH 4 + -sensitive Yangmai20 and NH 4 + -tolerant Xumai25, to NH 4 + stress to elucidate the mechanism of NH 4 + tolerance in wheat. Our results showed that NH 4 + stress had a significant adverse impact on the growth of wheat seedlings (Table 1, Figure 1), which is consistent with similar observations in other plant species (Chen et al, 2020;Guo et al, 2021;Tian et al, 2021). Notably, the NH 4 + -tolerant cultivar, Xumai25, exhibited a less reduction in root growth and an enhanced NH 4 + accumulation capacity than the NH 4 + -sensitive cultivar, Yangmai20, resulting in a superior overall growth of Xumai25 under NH 4 + stress.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we assessed the responses of two wheat cultivars, NH 4 + -sensitive Yangmai20 and NH 4 + -tolerant Xumai25, to NH 4 + stress to elucidate the mechanism of NH 4 + tolerance in wheat. Our results showed that NH 4 + stress had a significant adverse impact on the growth of wheat seedlings (Table 1, Figure 1), which is consistent with similar observations in other plant species (Chen et al, 2020;Guo et al, 2021;Tian et al, 2021). Notably, the NH 4 + -tolerant cultivar, Xumai25, exhibited a less reduction in root growth and an enhanced NH 4 + accumulation capacity than the NH 4 + -sensitive cultivar, Yangmai20, resulting in a superior overall growth of Xumai25 under NH 4 + stress.…”
Section: Discussionsupporting
confidence: 92%
“…Our results align with these findings, demonstrating the consistency of NH4 + effects across studies. Additionally, other NH4 + salts, such as those examined by Guo et al [14], also contribute to the reduction in root length. Specifically, a 72-hour exposure to NH4Cl led to a notable dose-dependent decline in length of root in rice seedlings, further substantiating the patterns observed in our study.…”
Section: Root Lengthmentioning
confidence: 92%
“…As reported by Liu et al (2021) , NH 4 + -grown cotton treated with urea shows around 50% reduction in Arg content and 2.5-fold higher PA (Spd + Spm; to be published as a separate article) as compared to those without urea provision; and such measurements are consistent with the observations of a marked transcriptional upregulation of four genes (i.e., ADC1 , ADC2 , SPDS , and SPMS ) that are required for Arg decomposition and PA conversion ( Liu et al, 2021 ). Since the expression of three high-affinity NH 4 + -transporter homologs (i.e., AMT1.1/1.2/1.3 ) remains generally low with/without urea supply to the ammonium media ( Liu et al, 2021 ), an internal PA elevation level by urea supply in plants should not much affect or repress AMT1s system involved in NH 4 + -detoxification, unlike the observation of thymol-ameliorated NH 4 + -stress via suppressing PA oxidase-derived H 2 O 2 and modulating AMT1s in rice ( Guo et al, 2021 ). Comparably, in the animal system, an interrelation between urea-cycle activity and PA biosynthesis has been well characterized in controlling certain critical cell processes.…”
Section: Polyamine Acts As a Significant Physiological Component In T...mentioning
confidence: 99%